Pemidanaan Terhadap Profesi Notaris Dalam Rangka Mewujudkan Perlindungan Hukum - Syafran S.; Fauzi Yusuf Hasibuan; Irhamsyah Irhamsyah (Postgraduate of Jayabaya University, 2020)
This research intends to examine the problematic of criminalization against the Notary profession in Indonesia. To analyze this problem, the researcher employs the theory of legal protection as Grand Theory, profession and professionalism theory as Middle-Range Theory, and criminalization theory as Applied Theory. The method employed in this research is juridical-normative method. The results of this study show the following conclusions. Firstly, criminalization against notary can only be carried out if it fulfills three conditions, namely the Notary violates the procedure of drawing up authentic deeds as regulated in UUJN (Law on Notary Profession), the notary violates the provisions of the criminal law as regulated in the Criminal Code, and the existence of the mens rea from the notary concerned. In making an official (ambtelijk) deed (drawn up by a notary), the Notary may be held liable for criminal liability for the material truth of the deed he made and can be determined as a perpetrator or accomplice of a criminal act. However, in the drafting of a party (partij) deed (drawn up before a notary), a notary may only be held liable for criminal liability for the formal aspects of the deed he made and can only be stipulated as an accomplish to a criminal act. Secondly, a more appropriate criminal justice model to be applied in the settlement of criminal cases involving the Notary in carrying out his duties and authority as a public official is a mediation of restorative justice-based penalty. In this model, sanctions are applied to perpetrators of crime not in the form of corporal punishment, imprisonment or confinement, but the obligation to provide compensation or restitution to victims of crime.